The relation between STAI anxiety score and chewing movement - Maruyama, Takao; Omae, Taizo; Ito, Hiroko; Nakaminami, Tadashi (Japanese Journal of Psychosomatic Dentistry, 1993)
This study investigated various kinds of parameters concerning chewing movement in relation to psychosomatic factors such as anxiety. Fifty Subjects (male: 46 female: 4, Average: 26.4 years old), studying in Osaka University, free of stomatognathic dysfunction signs participated in this study. At first, they answered a State-Trait Anxiety Inventory Form X questionnaire (STAI), and their chewing movements were recorded by a Sirognathograph Analysing System III. Then, the scale of State or Trait Anxiety was correlated with parameters of chewing movement ; rhythm, occluding points, shape of chewing pathway andmaximum speed were investigated. The results were as follows; 1) There was a positive correlations between the scale of the State Anxiety and the occluding phase period and a negative correlation with the maximal jaw opening. 2) Concerning the scale of Trait Anxiety there was a negative correlation with the amount of maximal jaw opening, and also a negative correlation with maximum jaw opening and closing speed. It was suggested that psychosomatic factors such as anxiety participate in chewing movement.